The Concept of Tawheed of Buginese People in the Ancient Manuscript Lontara Attorioloang Ri Wajo of West Kalimantan - Patmawati, Patmawati; Wahida, Besse (Al-Albab, 2018)
This paper discusses a tawheed concept of buginese people in the ancient manuscript, Lontara Attorioloang ri Wajo and focuses on the concept of al-uluhiyah and ar-rububiyah of Buginese people according to the manuscript. This work is based on research on manuscript through philology approach since Lontara Attorioloang ri Wajo is a handwriting manuscript written without punctuation (comma or full stop) and space. The concept of tawheed al-uluhiyah of buginese people in Lontara Attorioloang ri Wajo manuscript is shown in the form of testimony of the presence of Dewata Seuwwae or God the one; He begets not, nor was He begotten. The belief of the oneness of god is embodied in self-surrender and full obedience by performing worship qhairu mahda but not ibadah mahdah. This confession can be seen in 18 dialogues between Arung Matoa and an Arung from another place. The concept of tawheed ar-rububiyah in the manuscript is shown in the form of a belief that Dewata Seuwwae or the one God is a lord of the worlds; He determines all creatures’ destiny and prosperity. Further, the Buginese people’s belief in the oneness of God is shown by the agreement they have made, and Arung Matoa Toudamang’s message about how to behave toward god, other person, and nature. There are 8 dialogues in the form of agreement and pappaseng.